2014
DOI: 10.1371/journal.pone.0104310
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Effect of Catechol Is Related to Inhibition of Cyclooxygenase, Reactive Oxygen Species, ERK/p38 Signaling and Thromboxane A2 Production

Abstract: Catechol (benzenediol) is present in plant-derived products, such as vegetables, fruits, coffee, tea, wine, areca nut and cigarette smoke. Because platelet dysfunction is a risk factor of cardiovascular diseases, including stroke, atherosclerosis and myocardial infarction, the purpose of this study was to evaluate the anti-platelet and anti-inflammatory effect of catechol and its mechanisms. The effects of catechol on cyclooxygenase (COX) activity, arachidonic acid (AA)-induced aggregation, thromboxane B2 (TXB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…23 The branched ether 2,2-dimethoxybutane have been reported to be toxic to microbial membrane. 24 1,2-benzenediol is present in plant-derived products, such as vegetables, fruits, coffee, tea, wine, areca nut and cigarette smoke 25 among them include Diospyros kaki, 26 Annona senegalensis, 27 Petalostigma triloculare 23 among others. Report have shown that 1,2-benzenediol possess antimicrobials as well as antiplatelet 25,26 activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The branched ether 2,2-dimethoxybutane have been reported to be toxic to microbial membrane. 24 1,2-benzenediol is present in plant-derived products, such as vegetables, fruits, coffee, tea, wine, areca nut and cigarette smoke 25 among them include Diospyros kaki, 26 Annona senegalensis, 27 Petalostigma triloculare 23 among others. Report have shown that 1,2-benzenediol possess antimicrobials as well as antiplatelet 25,26 activity.…”
Section: Discussionmentioning
confidence: 99%
“…24 1,2-benzenediol is present in plant-derived products, such as vegetables, fruits, coffee, tea, wine, areca nut and cigarette smoke 25 among them include Diospyros kaki, 26 Annona senegalensis, 27 Petalostigma triloculare 23 among others. Report have shown that 1,2-benzenediol possess antimicrobials as well as antiplatelet 25,26 activity. Phenol, 2,4-bis (1, 1-dimethylethyl)-has also been reported in Scolopendra subspinispes with strong antioxidant activity, 28 Pereskia bleo with anticancer activity, 29 and strain of Pseudomonas monteilii PsF84 with antifungal activity, 30 Additionally, vitamin E identified two times at different retention times in this study is a well known antioxidant compound used for the treatment of various illnesses while N-Acetyl-Alpha-D-glucosamine has been used as safe alternative therapies for osteoarthritis,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 1.5 × 10 6 pulp cells were seeded onto 10‐cm culture dishes in 10 ml DMEM comprising 10% FBS. After cell attachment overnight, cells were exposed to fresh medium containing various concentrations of TGF‐β1 (0.5, 1, 5, 10 ng/ml) for 24 h. Then, culture medium was decanted and cells were washed with phosphate‐buffered saline and dissolved in lysis buffer containing 10 m m Tris–HCl, pH 7; 140 m m sodium chloride; 3 m m magnesium chloride; 0.5% NP‐40; 2 m m phenylmethylsulphonyl fluoride; 1% aprotinin; and 5 m m dithiothreitol (Chang et al , ,b, ). The same amount of proteins (30–50 μg/lane) in cell lysates was loaded for 12.5% sodium dodecyl sulphate–polyacrylamide gel electrophoresis, and transferred to a polyvinylidene fluoride membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, platelets will interact with the exposed subendothelial matrix,4, 5 leading to intraplatelet signaling and activation, which is associated with several events, including release of arachidonic acid from the membrane phospholipids 6, 7. The liberated arachidonic acid is metabolized by the cyclooxygenase enzyme and thromboxane A 2 (TXA 2 ) synthase, leading to the formation of TXA 2 8, 9, 10. TXA 2 , a well‐studied platelet agonist, is a labile lipid mediator that acts through binding to its G‐protein–coupled receptor11, 12, 13 (namely, the TXA 2 receptor [TPR]).…”
Section: Introductionmentioning
confidence: 99%